Comparison of Suprachoroidal Triamcinolone Injection with Intravitreal Bevacizumab Vs Intravitreal Bevacizumab only in Treatment of Refractory Diabetic Macular Edema - Muhammad Hamza Shahid, Faisal Rashid, Saba Tauqeer, Rabab Ali, Muhammad Talha Farooq, Nouman Aleem, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Macular edema due to diabetic retinopathy is among the most common causes of blindness in diabetics from working age group around the world . Diabetic macular edema which involves the center of the macula is among the major cause of visual decline in patients with diabetes mellitus. Intra-Vitreal Triamcinolone Acetonide with intravitreal Bevacizumab and intravitreal Bevacizumab only have been in practice as treatment options for cases not responsive to anti-vascular endothelial growth factor agents. Objective: To compare safety and efficacy profile of suprachoroidal injection of triamcinolone acetonide with intravitreal Bevacizumav Vs intravitreal injection of Bevacizumab alone in management of resistant diabetic macular edema. Patients & Methods: In this study, Fourty eyes of fourty patients who had resistant diabetic macular edema were randomly divided into two groups of 20 patients each (n=20) , our group A was injected with suprachoroidal triamcinolone acetonide 2 mg along with intravitreal Bevacizumab 1.25mg and the group B wasinjected with intravitreal Bevacizumab 1.25 mg only. Change in central macular thickness was observed after one month on Optical coherence tomography. Data was collected and analyzed by using SPSS software. Results: The mean age of subjects in this study was 58.46±3.62 years ( 30-65 years) . Out of 40 patients 26 were male patients and 14 were female .The mean decline (change) in central macular thickness in comparison to baseline thickness on OCT in group A was 113±10microns and mean change in the central thickness of macula on OCT in group B was 83+-10 microns with a p value of 0.01. Conclusion: Suprachoroidal triamcinolone acetonide with intravitreal bevacizumab is superior to intravitreal Bevacizumab alone in reducing central macular thickness among patients with resistant diabetic macular edema.